KESEHATAN DAN EKONOMI BERBASIS RUMAH TANGGA: PELATIHAN TEH KOMBUCHA SEBAGAI IMUNOMODULATOR DAN USAHA MANDIRI - Octarya, Zona; Yenti, Elvi; Lazulva, Lazulva (COMMUNITY SERVICE JOURNAL OF ECONOMICS EDUCATION, 2025)
Health and economic self-reliance are two essential aspects in improving the quality of life, particularly for housewives in RT 05 RW 05, Lembah Sari Subdistrict, Rumbai Timur. This community service activity aimed to provide training in the production of kombucha probiotic drinks, which function as immunomodulators and have the potential to serve as an additional source of income. The method used was Participatory Action Research (PAR), which actively involved the community throughout the entire process—from problem identification to reflection on outcomes. The training was conducted in three main stages: planning, implementation, and evaluation. The results of the activity showed an increase in the housewives' understanding of the benefits of kombucha and their ability to produce the drink independently.